2023
DOI: 10.1111/ijfs.16652
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum) peel extracts and their potential as antioxidant and antimicrobial agents for food applications: influence of pretreatment and extraction solvent

Itzel Yoali Hernández‐Montesinos,
David Fernando Carreón‐Delgado,
Erik Ocaranza‐Sánchez
et al.

Abstract: SummaryGarlic peel extracts are known to have excellent physiological activity but research on the pre‐processing of garlic peel (GP) to enhance their bioactivity is limited. The aim of this study was to evaluate the effect of two pretreatments applied to GP, such as fermentation with Lactobacillus plantarum and heat processing (10 min roasting), and two extraction solvents (70% v/v ethanol and methanol); on the total phenolic content (TPC), total flavonoid content (TFC), antioxidant capacity (AC) and antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Further, the non-volatile precursors were mainly gamma-glutamyl-S-allyl-L-cysteine and S-allyl-L-cysteine sulfoxide (alliin). Meanwhile, thiosulfinates (allicin), volatile organosulfur compounds (methyl allyl disulfide, methyl allyl trisulfide), and water-soluble organosulfur compounds are the main volatile precursors [57][58][59].…”
Section: Chemical Composition Of Garlic Peel Extractsmentioning
confidence: 99%
“…Further, the non-volatile precursors were mainly gamma-glutamyl-S-allyl-L-cysteine and S-allyl-L-cysteine sulfoxide (alliin). Meanwhile, thiosulfinates (allicin), volatile organosulfur compounds (methyl allyl disulfide, methyl allyl trisulfide), and water-soluble organosulfur compounds are the main volatile precursors [57][58][59].…”
Section: Chemical Composition Of Garlic Peel Extractsmentioning
confidence: 99%
“…Besides, ELNs also have some merits such as no toxicity, low immunogenicity, large production capability, ability of crossing the blood–brain barrier (BBB) but not the placenta, etc . Garlic is enriched in bioactive compounds, including allicin, alliin, diallyl disulfide, and quercetin, which play a pivotal role in the plant’s defense against pathogens, and has well-documented antimicrobial activity. Song et al found that a mannose-specific binding protein II lectin was highly expressed on the surface of garlic-derived ELNs (GELNs), which could recognize and bind with CD98 receptors on the surface of cells, thus significantly promoted the cell internalization of GELNs . GELNs also exhibited an anti-inflammatory effect by downregulating proinflammatory factors on the HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic is considered a nutritious food that might also have antimicrobial characteristics. (Hernández-Montesinos et al, 2023). The global price of garlic has been increasing during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%